The Wandering Officer - Grunwald, Ben (2020)
“Wandering officers” are law-enforcement officers fired by one department, sometimes for serious misconduct, who then find work at another agency. Policing experts hold disparate views about the extent and character of the wandering-officer phenomenon. Some insist that wandering officers are everywhere—possibly increasingly so—and that they’re dangerous. Others, however, maintain that critics cherry-pick rare and egregious anecdotes that distort broader realities. In the absence of systematic data, we simply do not know how common wandering officers are or how much of a threat they pose, nor can we know whether and how to address the issue through policy reform. In this Article, we conduct the first systematic investigation of wandering officers and possibly the largest quantitative study of police misconduct of any kind. We introduce a novel data set of all 98,000 full-time law-enforcement officers employed by almost 500 different agencies in the State of Florida over a thirty-year period. We report three principal findings. First, in any given year during our study, an average of just under 1,100 officers who were previously fired—three percent of all officers in the State—worked for Florida agencies. Second, officers who were fired from their last job seem to face difficulty finding work. When they do, it takes them a long time, and they tend to move to smaller agencies with fewer resources in areas with slightly larger communities of color. Interestingly, though, this pattern does not hold for officers who were fired earlier in their careers. Third, wandering officers are more likely than both officers hired as rookies and those hired as veterans who have never been fired to be fired from their next job or to receive a complaint for a “moral character violation.” Although we cannot determine the precise reasons for the firings, these results suggest that wandering officers may pose serious risks, particularly given how difficult it is to fire a police officer. We consider several plausible explanations for why departments nonetheless hire wandering officers and suggest potential policy responses to each